The New Standard for Drinking Water - V. Goncharuk (Journal of Chemistry)
The main positions of the new standard on drinking water are provided. The inconsistency of existing approaches to the assessment including methodology of drinking water quality was substantiated. The main advantage of the new standard is the inclusion of integral methods of water quality, universal for all kinds and types of toxic compounds, irrespective of their origin and nature of the action.